Perception of women on the care in the childbirth: contributions to nursing - doi: 10.4025/actascihealthsci.v35i2.10442 - Brasil, Eysler Gonçalves Maia; Queiroz, Maria Veraci Oliveira; Fernandes, Ana Fátima Carvalho; Costa, Rachel Franklin da; Xavier, Emanuelle de Oliveira (Acta Scientiarum. Health Sciences, 2013)
This study aimed to understand the perception of women regarding the care received during delivery/birth, and discuss the precepts of integrality according to humanization of care. This was a qualitative research study, performed at a tertiary care public hospital in Fortaleza, Ceará State, Brazil. The research subjects were 13 women whose deliveries were made in that unit, and invited to take part in the focal group featuring the following themes: women’s perception about the care received; the relationship with the professionals of the obstetrics and neonatal units; satisfaction with the assistance provided by the hospital at the time of delivery and birth. The data were subjected to thematic category content analysis. The women emphasized the good assistance received, consisting of care and dedication by the professionals. They showed the importance of correct and detailed information, but observed miscommunication and lack of a user-professional bond, due to the large number of professionals working in the unit. Nevertheless, they were satisfied with the assistance received. Positive aspects of the assistance were evidenced, but it is essential that the professional-user relationship be improved, in order to meet the humanization perspectives of care, which are also anchored on integrality.